2018
DOI: 10.1111/jpi.12493
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves insulin resistance and hepatic steatosis through attenuation of alpha‐2‐HS‐glycoprotein

Abstract: Melatonin plays an important role in regulating circadian rhythms. It also acts as a potent antioxidant and regulates glucose and lipid metabolism, although the exact action mechanism is not clear. The α2-HS-glycoprotein gene (AHSG) and its protein, fetuin-A (FETUA), are one of the hepatokines and are known to be associated with insulin resistance and type 2 diabetes. The aim of this study was to determine whether melatonin improves hepatic insulin resistance and hepatic steatosis in a FETUA-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 49 publications
3
58
0
Order By: Relevance
“…The JNK pathway is known to be stimulated by oxidative stress (Mota, Banini, Cazanave, & Sanyal, ) and implicated in hepatocyte apoptosis induced by saturated free fatty acids. Heo found that oral treatment of 100 mg/kg/day melatonin for 10 weeks to HFD‐induced NAFLD mice improved insulin sensitivity and decreased plasma insulin (Heo, ). Melatonin has also been reported to reduce phosphorylation of JNK1/2 in a mouse model of HFD‐induced NAFLD (Sun et al, ).…”
Section: The Role Of Oxidative Stress In Nafld and Nash And The Effecmentioning
confidence: 99%
See 1 more Smart Citation
“…The JNK pathway is known to be stimulated by oxidative stress (Mota, Banini, Cazanave, & Sanyal, ) and implicated in hepatocyte apoptosis induced by saturated free fatty acids. Heo found that oral treatment of 100 mg/kg/day melatonin for 10 weeks to HFD‐induced NAFLD mice improved insulin sensitivity and decreased plasma insulin (Heo, ). Melatonin has also been reported to reduce phosphorylation of JNK1/2 in a mouse model of HFD‐induced NAFLD (Sun et al, ).…”
Section: The Role Of Oxidative Stress In Nafld and Nash And The Effecmentioning
confidence: 99%
“…Melatonin inhibits ischemia-induced overproduction of iNOS and NO (Rodriguez-Reynoso et al, 2001). Melatonin also reduces NF-kB activation (Kang et al, 2011) and increases nuclear translocation of Nrf2 with subsequent induction of HO-1 (Kang & Lee, 2012), GST (Kireev et al, 2013), and NQO1 (Chen et al, 2016) TABLE 2 Protection role of melatonin against liver ischemia-reperfusion injury (IRI) and the level of oxidative stress 100 mg/kg/day melatonin for 10 weeks to HFD-induced NAFLD mice improved insulin sensitivity and decreased plasma insulin (Heo, 2017).…”
Section: The Role Of Oxidative Stress In Nafld and Nash And The Effmentioning
confidence: 99%
“…In our previous research, melatonin ameliorates metaflammation‐induced pyroptosis through intracellular nuclear factor kappa‐light‐chain‐enhancer of activated B cell/Gasdermin D signal in adipose tissue, and it prevents adipocyte dysfunction under circadian rhythm disorder . On the other hand, melatonin has also been confirmed to protect liver during metabolic syndrome through various defined mechanisms . Melatonin triggers ER‐ and autophagy‐induced apoptosis in liver cancer, while it inhibits hepatocellular carcinoma proliferation and invasiveness via various transcription factors and signaling pathways .…”
Section: Introductionmentioning
confidence: 97%
“…30,31 In obese individuals and mice models, melatonin has also been identified to control the development of obesity, improve lipid metabolism, ameliorate hepatic oxidative stress and mitochondrial dysfunction, 3,4,[32][33][34][35][36] and alleviate local/systematical inflammation in different tissues and organs. 28,37,38 In our previous research, melatonin ameliorates metaflammation-induced pyroptosis through intracellular nuclear factor kappa-light-chain-enhancer of activated B cell/Gasdermin D signal in adipose tissue, and it prevents adipocyte dysfunction under circadian rhythm disorder. 28,39 On the other hand, melatonin has also been confirmed to protect liver during metabolic syndrome through various defined mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation